Morphology of Halophila ovalis (R.Br.) Hook. f. from Peninsular and East Malaysia - Loganathan, Annaletchumy; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah; Arshad, Aziz (Universiti Putra Malaysia Press, 2005)
Halophila ovalis plants were collected from six locations with different habitat characteristics; Merambong, lohore ofPeninsular Malaysia (sub-tidal shoal), Teluk Sepinong of Sabah (sub-tidal estuary), Pulau Gaya, Sabah (subtidal degraded coral), Merchang, Terengganu (inter-tidal lagoon), Teluk Kemang, Negeri Sembilan (inter-tidal degraded coral platform) and Punang, Sarawak (inter-tidal beach front). Based on the leaf dimensions (length and width) and number of paired cross-veins, three Halophila ovalis variants can be distinguished; big, intermediate and small-leaved. The big-leaved H. ovalis are found at sub-tidal areas e.g. Merambong, Teluk Sepinong, while intermediate- and small-leaved variants are from inter-tidal areas that are exposed to air for 3 to 4 hours during low tides e.g. Punang, Merchang, Teluk Kemang and Pulau Gaya. The salinity and depth in a particular habitat contribute to the variability in shapes and dimension of leaf sizes. Halophila ovahs leaves showed diverse shapes from ovate, obovate, oblong to spathulate. At deeper depths, turbid water and muddy substrate, leaves of H. ovalis are elongated in shape and with longer petiole length. Halophila ovalis in Malaysia exhibit morphological variability particularly in the leaves in response to the different environmental factors in the various habitats.